THE INTIFADA AS THE STRUGGLE FOR EMANCIPATION OF ISRAELI DOMINATION AND THE INSERTION IN THE INTERNATIONAL SYSTEM - Brito Santana Leal, Juliana (2024)
This article proposes to expose the form of domination to which Palestine is still subject and the different forms of oppression that affect these people. With the Intifada as a mechanism for attempting an emancipatory struggle, Palestine has strived to become part of the System. The article intends to raise reflection on how emancipation can be achieved from the civil uprising, the Intifada, contrary to Israeli subjugation, and how this uprising can lead to a probable subjugation, no longer of Israel, but of the System itself.